How To Identify Spam Blockchain Projects - Faisal M. Alshehri , Turki I. Alshamrani , Meteb R. Alqahtani , Suliman O. Alanazi; Adel R. Alharbi (Migration Letters, 2024)
Decentralized Finance (Defi) is an ecosystem that operates peer-to-peer without the need for an intermediary such as banks. Defi relies on blockchain technology to manage financial transactions such as transfers, withdrawals, and deposits. It is an open-source system that anyone can follow, unlike banks. Defi is rapidly advancing and reshaping the financial industry by providing pio-neering, transparent, and environmentally sustainable cash solutions. In our previous study, we noticed that the world of Defi is large and complex in terms of the projects presented, and the worrying thing is that some of these proposed projects are not safe enough t[1]o work on. In this work we comprehensively examine and perform a comparative evaluation of each toolkit, evaluating their advantages and disadvantages. In addition, coding techniques are used to evaluate the advantages and disadvantages of Defi projects about their security. 100 smart contracts were analyzed using 10 tools, the top five high-risk tokens were analyzed, five risk-free tokens were analyzed, and Defi platforms were analyzed using Scam Detector.